Russia and the Debate of the NATO Enlargement in the 1990s - Lengyel, Gábor (Acta Scientiarum Socialium, 2012)
One of the most important diplomatic debates of the 1990s evolved around the eastern enlargement of the NATO. In the early years of the foreign policy of the Middle-Eastern countries by now free from soviet influence one major issue was to adapt themselves to the post-cold war world order. All of the countries involved – the Czech Republic, Poland and Hungary in the first round – soon realized that their only option was to get integrated into the western organizations, to NATO in particular. The leading politicians of this organization had their doubts about these countries’ capability to adapt to the already developed system of the organization. This is mainly illustrated by the fact that until the middle of the decade there was a lack of real commitment to the enlargement of the alliance. The PfP document of January 1994 may be regarded as a breakthrough. The diplomacy of Moscow became more and more dismissive as to the idea of the eastern enlargement of the NATO. Within a few months an attitude that regarded Russia joining the NATO as a possible perspective gave way to the total rejection of the enlargement. This study aims at exploring the determining points of this debate mainly in the light of the most important documents.
Keywords: NATO enlargement; Russia; foreign policy; Central and Eastern Europe